Measuring moral disengagement with a situational judgment test: Advancing the assessment of an important workplace construct. (8th December 2020) - Fisher, David M.; Good, Stephen; Toich, Margaret J.; Schutt, Elizabeth
Abstract: Moral disengagement (MD) has been characterized as a uniquely important predictor of counterproductive work behaviors (CWBs). This study describes the development and validation of a situational judgment test (SJT) for measuring MD in the workplace, which offers potential advantages over existing Likert‐type scales. The development/validation efforts involved two independent rounds of subject‐matter expert (SME) review and data collected from three independent samples. The resulting test, labeled the MD‐SJT, displayed high reliability, was related to an established measure of MD as well as hypothesized personality variables, and was incrementally predictive of CWBs above the established measure of MD. This study advances knowledge pertaining to the assessment of MD, which is a critically important construct in the workplace.